Optimal planning of CHP-based microgrids considering DERs and demand response programs - Qaeini, Saeid; Nazar, Mehrdad S.; Shafie-khah, Miadreza; Osório, Gerardo J.; Catalão, João P. S. (IEEE, 2020)
This work addresses a stochastic framework for optimal operation and long-term expansion planning of combined heat and power based microgrid as a part of an active distributing system. The microgrid utilizes renewable energy sources, electricity and heat generation units, energy storage systems, and demand response programs. The proposed model determines the optimal location and capacity of the electrical and thermal facilities, and it considers the impact of renewable energy sources and demand response on the expansion-planning problem. A stochastic mixed-integer linear programming formulation is utilized to minimize the investment and operation costs of system for five years. To evaluate the effectiveness of the proposed model, the algorithm is assessed for the 9-bus system and the 33-bus IEEE test systems. The results demonstrate that the utilization of the proposed algorithm reduces the operational cost and increases system revenues.
Keywords: microgrid; combined heat and power; renewable energy; distributed generation; expansion planning; demand response; fi=Sähkötekniikka|en=Electrical Engineering|